Interaction of the Bovine Papillomavirus E6 Protein with the Clathrin Adaptor Complex AP-1 - Tong, Xiao (American Society for Microbiology, 1998)
The E6 gene of the bovine papillomavirus type 1 (BPV-1) is expressed in fibropapillomas caused by BPV-1 and in tissue culture cells transformed by BPV-1. It encodes one of the two major oncoproteins of BPV-1. In this study, we demonstrate an interaction between the BPV-1 E6 protein and AP-1, the TGN (trans-Golgi network)-specific clathrin adaptor complex. AP-1 is a four-subunit protein complex required for clathrin-mediated cellular transport from the TGN. The AP-1/E6 interaction was observed in vitro and in cells. The E6 binding site on AP-1 was mapped to the N-terminal trunk domain of the γ subunit. BPV-1 E6 preferentially associated with membrane-bound AP-1 in cells but not with free cytosolic AP-1. BPV-1 E6 was further shown to be recruited to isolated Golgi membranes and to copurify with clathrin-coated vesicles. The recruitment of BPV-1 E6 to Golgi membranes was AP-1 independent, but the E6 interaction with AP-1 was required for its association with clathrin-coated vesicles. Furthermore, AP-1 proteins could compete with BPV-1 E6 for binding to Golgi membranes, suggesting that the recruitment of BPV-1 E6 and AP-1 to Golgi membranes involves a common factor. Taken together, our results suggest that cytosolic BPV-1 E6 is first recruited to the TGN, where it is then recognized by membrane-bound AP-1 and subsequently recruited into TGN-derived clathrin-coated vesicles. We propose that BPV-1 E6, through its interaction with AP-1, can affect cellular processes involving clathrin-mediated trafficking pathway.